2011
DOI: 10.1021/ic101981x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Optical Properties of LiEu(PO3)4Nanoparticles

Abstract: A wet chemical approach was employed for the preparation of LiEu(PO(3))(4) nanoparticles. XRD, Raman spectroscopy, TEM, SAED, and IR measurements were used in order to determine the crystal structure and morphology of the obtained product. Complete optical studies including absorption, excitation, emission, and kinetic measurements were performed. At least two components of the (5)D(0) → (7)F(0) transition were found, indicating the existence of more than one crystallographic position of the Eu(3+) ions. Asymm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…The enhanced PL intensities should be mainly due to achievement of the β‐TCP phase in the HA/β‐TCP system, which was also consistent with the XRD results (Figure ). It can also be observed that the relative intensity of the 5 D 0 → 7 F 2 emission band in the Eu‐doped F‐HA was much higher than that associated with the 5 D 0 → 7 F 1 transition, which is expected for Eu 3 + located in the noncentrosymmetric site, as is often the case with Eu‐doped HA annealed at high temperature …”
Section: Resultsmentioning
confidence: 71%
“…The enhanced PL intensities should be mainly due to achievement of the β‐TCP phase in the HA/β‐TCP system, which was also consistent with the XRD results (Figure ). It can also be observed that the relative intensity of the 5 D 0 → 7 F 2 emission band in the Eu‐doped F‐HA was much higher than that associated with the 5 D 0 → 7 F 1 transition, which is expected for Eu 3 + located in the noncentrosymmetric site, as is often the case with Eu‐doped HA annealed at high temperature …”
Section: Resultsmentioning
confidence: 71%
“…Similar to the PL emission characteristic of Eu-doped Si-HA synthesized by three methods without thermal annealing, the luminescent emission intensity was increased significantly on application of thermal annealing up to 1000 • C. Among the different synthesis methods, the hydrothermal methods reveals the best light emission represented by high PL intensity and narrow PL spectra. It is generally accepted that when the energy transfer from the matrix to the activator is optimized, the phosphor will emit strong emission with a sharp and narrow band spectrum; otherwise, they will emit relatively weak intensity with a broad emission band [1,20]. The coprecipitation specimen showed a long nanowire microstructure ( Fig.…”
Section: Effect Of Synthesized Methodsmentioning
confidence: 99%
“…The development of new materials and synthesis techniques for improving the light emission performances and long-term stability of devices is one of the most active research areas in optoelectronic industries and nanomedicine [1,2]. Fundamentally, the light emission ability of materials is strongly affected by their host matrices, activators, defects, and crystallinity of materials [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…[8,15] In this article we have focused on the sol-gel synthesis, structural, and optical characterization of Eu x Zn 1-x Al 2 O 4 (x = 0.005-0.01) nanoparticles. [4] Afterglow luminescence occurring in lightly Eu-doped samples was also investigated and explained. Detailed characterization of the luminescence properties of the Eu x Zn 1-x Al 2 O 4 nanoparticles was performed on the basis of their excitation and emission spectra.…”
Section: Introductionmentioning
confidence: 99%